The imperative of necessity and possible territorialities: the experience of homeless people attending a Brazilian Psychosocial Care Center - Turbiani Santana, Larissa; Maciel Nunes Gonçalves, Arthur; Bulhões Nunes Vaz, Caroline (Geografares, 2023)
This study aimed to explore the territoriality of homeless people who use the Psychosocial Care Center in São Paulo, Brazil. Semi-structured interviews were conducted with these individuals to investigate how they build their sense of territoriality in the city and what forms of citizenship are experienced in a homeless situation. The analysis of their narratives revealed the intricate nature of social exclusion and the lack of full citizenship realization. It highlighted the dialectical tension between public and private spheres, the constraining effect of class structure, and limited access to spatial mobility and mental health services. The findings demonstrated that territorialities were largely confined to the realm of basic needs and the struggle for survival